2018
DOI: 10.1097/inf.0000000000001836
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Criteria for Bronchiolitis

Abstract: Background: Admission criteria and standardized management strategies for bronchiolitis are addressed in several guidelines and have shown to be beneficial; however, guidance regarding discharge criteria is limited and widely variable. We assessed the impact on clinical outcomes of a discharge protocol for children <2 years of age hospitalized with bronchiolitis in a tertiary care pediatric hospital. Methods: In October 2013, a protocol to standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…One study found differences in LOS and hospital costs correlated to differences in care practices between hospitals [ 35 ]. Another study found reduction in LOS after introduction of discharge criteria [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study found differences in LOS and hospital costs correlated to differences in care practices between hospitals [ 35 ]. Another study found reduction in LOS after introduction of discharge criteria [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most parents of hospitalised children reported that they would have preferred to have been given clear discharge criteria by their physicians. This could be challenging to implement, as there are no universal discharge criteria for bronchiolitis and subsequent practice variations 31 . Paediatricians should try to identify potential discharge criteria with the parents, at the time of admission, and adapt them to each patient and family.…”
Section: Discussionmentioning
confidence: 99%
“…This could be challenging to implement, as there are no universal discharge criteria for bronchiolitis and subsequent practice variations. 31 Paediatricians should try to identify potential discharge criteria with the parents, at the time of admission, and adapt them to each patient and family.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the comments from Korppi in relation to our recently published study describing the utility of established discharge criteria for infants and young children with bronchiolitis. 1 Bronchiolitis remains the number one cause of hospitalization in infants and is associated with significant morbidity, 2 yet, despite being one of the most common diseases of childhood, we lack a standard definition, with some countries including in their guidelines infants only and others children up to 2 years of age. 35 Nonetheless, as mentioned by Korppi, the major impact of respiratory syncytial virus bronchiolitis occurs during the first year of life, and the peak of severe respiratory syncytial virus (RSV) disease in the first 6 months of life.…”
Section: To the Editorsmentioning
confidence: 99%
“…In our study, the majority of children [85% (946/1118) in Infectious Diseases (ID), where the discharge protocol was used, and 73% (509/695) in non-ID units] were younger than 12 months of age, while the cohort of infants younger than 6 months of age represented 61% (687/1118) of ID patients and 47% (330/695) of children with bronchiolitis discharged from non-ID units. 1 If we were to limit the analyses to this very young population, we would have left out of the study half of the children hospitalized with this disease. The discharge protocol that we used included different parameters that were age-specific.…”
Section: To the Editorsmentioning
confidence: 99%